Diagnostic laparoscopy findings in pelvic pain among the women attending Gynecology OPD at Dhulikhel Hospital - Yadav, Arun; Tamrakar, Suman Raj (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To evaluate the laparoscopic findings in women with pelvic pain.Methods: A prospective study conducted in Department of Obstetrics and Gynecology at Dhulikhel Hospital from March 2017 to December 2018. All women with pelvic pain, ultrasound evaluation and laparoscopic procedure at the hospital were taken. Data entered in SPSS 23 and analyzed using descriptive parameters.Results: Maximum number of cases of pelvic pain belonged to 21-30 years, most of them were parous with mean duration of pain of 16.48±4 months. The mean age and parity of the patients was 34±5 years and 1.74 respectively. The most common complaint was dysmenorrhea (33.3%) followed by abnormal vaginal discharge (31.7%). On clinical examination, pelvic tenderness was observed in majority (21.7%) of cases.On laparoscopic examination, normal finding were seen in 41.7% cases followed by pelvic inflammatory disease (19.2%), endometriosis (17.5%), pelvic adhesion (12.5%), retroverted uterus (2.5%). PCOS, pelvic congestion and fimbrial cyst were seen in 1.7% each. Pyosalphinx and twisted ovary were seen in 0.8% each.Conclusions: Laparoscopy serves as diagnostic as well as a therapeutic modality of management in chronic pelvic pain.